Too risky, too large, too late, or too mild—Reasons for not treating ischemic stroke patients and the related outcomes - Behrndtz, Anne Brink; Damsbo, Andreas Gammelgaard; Blauenfeldt, Rolf Ankerlund; Andersen, Grethe; Speiser, Lasse Ole; Simonsen, Claus Ziegler (Frontiers in Neurology, 2022)
Background Despite effective treatments, many patients are still not offered reperfusion therapy for acute ischemic stroke. Methods We present a single-center observational study on acute ischemic stroke patients, who presented as candidates for reperfusion therapy but were deemed ineligible after work-up. Reasons for non-treatment were obtained by studying patient files and subsequently grouped into “too risky” (e.g., anticoagulant use, comorbidities), “too large” (large infarct), “too late” (late presentation of stroke and wake-up strokes), or “too mild” (clinically mild/remitting symptoms). Modified Rankin scale (mRS) score was prospectively collected in all patients by a structured telephone interview. All non-treated patients with a National Institute of Health Stroke Scale (NIHSS) score of 0–5 were compared with a similar cohort that was treated. Results Of 529 patients with acute ischemic stroke arriving as reperfusion therapy candidates, 198 (37.4%) were not treated. The majority (42%) were not treated due to admission outside the treatment window (too late) and 24% had absolute contraindications (too risky). Only 8% was excluded because their infarct was too large [median Alberta Stroke Program Early CT score 3 (2–4)]. In the “too mild” group (14%) the percentage of patients not being independent at 90 days was 30%. The adjusted odds ratio for a better outcome (lower mRS) among treated patients with NIHSS 0–5 compared with non-treated was 1.93 (95% confidence interval 1.15–3.23). Conclusion Presenting outside the treatment window is still the most common reason for not receiving therapy. Our study suggests a benefit of thrombolysis for patients with mild symptoms.